Extranodal nasofacial natural Killer/T-cell lymphoma: Our experiences at a tertiary care hospital of Eastern India - Santosh Kumar Swain; Mahesh Chandra Sahu; Manash Ranjan Baisakh (Apollo Medicine, 2018)
Background: Natural killer (NK)/T-cell lymphoma is a rare nonHodgkin's lymphoma originating in the nasofacial area including nasal cavity and paranasal sinuses. NK/T-cell lymphoma has an aggressive clinical course with unfavorable prognosis. Objective: Analysis of the etiopathogenesis, clinical profile, diagnostic difficulties, treatment options, and outcome in patients with NK/T-cell lymphoma of the sinonasal area. Materials and Methods: This is a retrospective observational study conducted over the period January 2012–December 2017. Age, gender, clinical presentation, histological diagnosis, radiological presentations, and immunophenotype characteristics were taken into consideration. Results: There were six patients, i.e., four males and two females with the common symptom were nasal obstruction (78%), nasal discharge (68%), and nasal bleeding (58%). The diagnosis was established by histopathological examination and immunohistochemistry. Computed tomography scan was done in all patients. Five patients were treated with chemoradiation one patient died after 6 months of treatment. Conclusion: Nasofacial NK/T-cell lymphoma is a rare clinical entity. Diagnosis is based on histopathological examination, immunophenotype, and molecular characteristics. It is an aggressive lymphoma which needs multidisciplinary approach. Its prognosis is poor. Optimal management of NK/T-cell lymphoma in the nasofacial area should be based on multidisciplinary approach among best outcome. Practicing physicians need to be aware of this nonspecific presentation of this lesion.